HUBUNGAN DUKUNGAN KELUARGA DENGAN KEMANDIRIAN PERAWATAN DIRI ANAK RETARDASI MENTAL - rahmadani, elsi; Sari, Gita Maya; Gito, Ariyus Popsi (STIKES Syedza Saintika Padang, 2024)
Children with mental retardation are children with below average IQ with the inability to carry out daily activities and maintain self-care and need family support. The purpose of this study was to analyze the relationship between family support and self-care independence in children with mental retardation at SLB Negeri in Bengkulu. This study is a type of quantitative correlation research with a cross-sectional analysis design. The sample in this study was 43 respondents from parents of children with mental retardation at SLB Negeri Bengkulu with a purposive sampling technique. Data collection using a questionnaire on family support and self-care independence and data analysis using the Chi-Square test. The results showed that 51.2% of respondents had less family support and (51.2%) had good self-care independence in children with mental retardation at SLB Negeri Bengkulu. The results of the Chi-Square statistical test showed p = 0.022 <0.05. The conclusion is that there is a relationship between family support and self-care independence in children with mental retardation at SLB Negeri Bengkulu. It is hoped that families can provide and improve good support for children with mental retardation by providing informational, emotional, assessment and instrumental support.Key Word : Family Support, Self-Care Independence, Mental Retardation